The economic impact of enoxaparin versus unfractionated heparin for prevention of venous thromboembolism in acute ischemic stroke patients - Pineo GF; Lin J; Annemans L (Dove Medical Press, 2012)
Graham F Pineo1, Jay Lin2, Lieven Annemans31Department of Medicine, University of Calgary, Calgary, Alberta, Canada; 2Novosys Health, Flemington, NJ; 3Department of Medicine, Ghent University, Ghent and Brussels University, Brussels, BelgiumAbstract: Venous thromboembolism (VTE) is a common complication after acute ischemic stroke that can be prevented by the use of anticoagulants. Current guidelines from the American College of Chest Physicians recommend that patients with acute ischemic stroke and restricted mobility receive prophylactic low-dose unfractionated heparin or a low-molecular-weight heparin. Results from clinical studies, most recently from PREVAIL (PREvention of Venous Thromboembolism After Acute Ischemic Stroke with LMWH and unfractionated heparin), suggest that the low-molecular-weight heparin, enoxaparin, is preferable to unfractionated heparin for VTE prophylaxis in patients with acute ischemic stroke and restricted mobility. This is due to a better clinical benefit-to-risk ratio, with the added convenience of once-daily administration. In line with findings from modeling studies and real-world data in acutely ill medical patients, recent economic data indicate that the higher drug cost of enoxaparin is offset by the reduction in clinical events as compared with the use of unfractionated heparin for the prevention of VTE after acute ischemic stroke, particularly in patients with severe stroke. With national performance measures highlighting the need for hospitals to examine their VTE practices, the relative costs of different regimens are of particular importance to health care decision-makers. The data reviewed here suggest that preferential use of enoxaparin over unfractionated heparin for the prevention of VTE after acute ischemic stroke may lead to reduced VTE rates and concomitant cost savings in clinical practice.Keywords: acute ischemic stroke, cost savings, enoxaparin, unfractionated heparin, venous thromboembolism